Proteostasis as a Sentry for Sperm Quality and Male Fertility - Sutovsky, Peter; Zelenkova, Natalie; Postlerova, Pavla; Zigo, Michal (Advances in experimental medicine and biology, 2025)
In the last two decades, a school of thought emerged that perceives male reproductive health, testicular function, and sperm output as a sentry for general, somatic health. Large-scale epidemiologic studies have already linked the reduced sperm count to increased risk of chronic somatic disease (e.g., cancer, cardiovascular, neurological and bone diseases), yet most of these studies have not taken full advantage of advanced andrological analysis. Altered proteostasis, i.e., the disbalance between protein synthesis and turnover, is a common denominator of many diseases, including but not limited to cancer and neurodegenerative diseases. This chapter introduces the concept of cellular proteostasis as a measure of sperm structural and functional integrity and an endpoint of varied impacts on spermiogenesis and sperm maturation, including heritability, general health, lifestyle, and occupational and environmental reprotoxic exposure. Special consideration is given to small molecule protein modifiers, sperm-binding seminal plasma proteins, zinc-interacting proteins, and redox proteins responsible for the maintenance of protein structure and the protection of spermatozoa from oxidative damage. While the main focus is on human male infertility, serious consideration is given to relevant animal models, and in particular to male food animals with extensive records of fertility from artificial insemination services. Altogether, the proteostatic biomarker discovery and validation studies set the stage for the integration of proteomics of sperm proteostasis with genomic and high throughput phenomic approaches to benefit both human and animal reproductive medicine.
Keywords: Proteasome; Ubiquitin; Infertility; Fertility; Male; Infertility, Male; homeostáze proteinů; spermatogeneze; Spermatozoa; Omics; Spermatogenesis; mužské pohlaví; fertilita; Animals; Sperm; lidé; Biomarker; Humans; zvířata; Proteostasis; spermie; Thioredoxin; mužská infertilita; Seminal plasma